Age at menarche and ischemic heart disease: An update mendelian randomization study - Chen, Jing; Chen, Heng; Zhu, Qiaozhen; Liu, Qiannan; Zhou, Yan; Li, Lan; Wang, Yan (Frontiers in Genetics, 2022)
Background: Although earlier menarche age has been associated with is-chemic heart disease in previous observational studies, the relationship's cau-sation has not been shown. Through two-sample mendelian randomization (MR), we were able to define the causal connection. Methods: We performed Mendelian Randomization (MR) analysis to ex-plore the associations between genetically predicted AAM and IHD. Sum-mary-level databases for exposure and outcome were selected from the MR-Base database (https://gwas.mrcieu.ac.uk/). Single-nucleotide polymorphisms (SNPs) connected to AAM at genome-wide significance level (P < 5 × 10−8) were considered as instrumental variables (IVs). We used four methods to pool MR estimates, including fixed-effects inverse variance weighting (fe-IVW), multiplicative random-effects inverse variance weighting (mre-IVW), weighted median (WM), and MR-Egger regression methods. Sensitivity anal-yses were performed to evaluate the robustness of the results. PhenoScanner searches and Multivariable mendelian randomization (MVMR) analysis was used for assessing confounders. Results: 117 SNPs significantly correlated with AAM were screened as in-struments, the results of three main methods showed that genetically earlier AAM may have a causal effect on the higher risk of IHD (fe-IVW: OR = 0.80, 95% CI: 0.72–0.88, P < 0.001; mre-IVW: OR = 0.80, 95% CI: 0.70–0.90, P < 0.001; WE: OR = 0.79, 95% CI: 0.66–0.93, P = 0.006). These results were consistent across sensitivity analyses. MR analysis revealed that there was still a relationship between AAM and IHD even when pleiotropic SNPs of confounders were removed employing PhenoScanner searches. In MVMR, the significant association remained after adjusting for biological sex, but it was attenuated with adjustment of body mass index including childhood and adult. Conclusion: Our MR analysis revealed a substantial genetically deter-mined confounder-mediated relationship between an increase in genetically predicted AAM and a lower risk of IHD. By addressing the intervention of body mass index, the risk of IHD may be lowered. Keywords: age at menarche, ischemic heart disease, Mendelian randomi-zation, causality